Professor A. M. Seagal is one of the first Russian cardiologists and arrhythmologists - L. M. Makarov (Российский кардиологический журнал, 2024)
Professor Alexander M. Seagal (1887–1968), was one of the first Russian cardiologists to identify cardiac arrhythmias as a separate independent problem in cardiology. In addition to numerous works on various issues of therapy and cardiology, he is the author of apparently the first Russian monograph on arrhythmology, "Rhythms of Cardiac Activity and Their Disorders," entirely devoted to cardiac arrhythmias and which went through two editions in Soviet times (1935 and 1958). An analysis of the mechanisms of not only pathological rhythms, but also physiological ones was carried out, an original clinical and electrocardiographic classification of bradycardias ("neurogenic" and "myogenic") and paroxysmal tachycardias was given, the electrophysiological and pathohistological basis of arrhythmias known at that time and methods of their treatment were analyzed. The book shows variants of arrhythmias that are still rare today ("cardiac alternation", etc.), and describes clinical variants of paroxysmal tachycardias, including atypical ones — induced by allergic triggers. In all cases of clinical examples, not only the clinical description and ECG picture of the arrhythmia are provided, but also the necessary therapeutic measures and prognosis. The clinic of arrhythmogenic syncope and other arrhythmic symptoms, which are still relevant in our time, is analyzed. Being a famous music connoisseur, A. M. Seagal used an original approach to recording the tones and rhythms of the heart, using a musical staff. Many clinical observations and conclusions are interesting and relevant in our time. A. M. Seagal was undoubtedly the one who stood at the origins of Russian arrhythmology, as a separate direction in cardiology.